Investigating the Facilitating and Inhibiting Factors of Clinical Education from the Perspective of Speech Therapy for Instructors and Students in 2020 - Zahra Rouhipour; Parvane Rahimifar; Younes Amiri-Shavaki; Maryam Dastourpour; Negin Moradi (Zanjan University of Medical Sciences and Health Services, 2021)
Background and Aim: Clinical education is a very important and effective part in speech therapy training, without that, it will be very difficult and impossible to train capable and qualified people. It is necessary to investigate the facilitators and deterrents to the quality and quantity of clinical education in the field of speech therapy to study educational problems and provide educational programs in the future. Methods: This is a descriptive-analytical cross-sectional study. 62 undergraduate students and 41 speech therapy instructors (41 people) were included in the study. They completed the consent form and a 62-item questionnaire of facilitators and inhibitors for clinical education. Data were analyzed using SPSS software version 22. Findings: 62 students with a mean age of 22.53 ± 1.9 and 41 instructors with a mean age of 36.29 ± 9.9 were studied. According to both groups, the most important facilitating factors were the area of ​​"facilitating characteristics of coaches and instructors" and the most important deterrents were the area of ​​"student dissatisfaction with the way practical and theoretical courses are presented". Based on the results of the independent t-test, in some facilitating and inhibiting factors, there was a significant difference between the opinions of the instructor and the student (p≤0.001). Conclusion: The most important area of facilitating clinical education is the use of experienced and responsible instructors who have passed appropriate in-service courses in clinical education. The quality of education is necessary to make decisions. It is also necessary to equip the physical spaces of clinics and their facilities and to establish a suitable time interval for presenting practical and theoretical courses